PERTUMBUHAN IKAN BARONANG LINGKIS, Siganus Canalicullatus (Park, 1797), DI PERAIRAN PANTAI UTARA KABUPATEN KEPULAUAN SELAYAR, SULAWESI SELATAN - Omar, Sharifuddin Bin Andy; Fitrawati, Rahmi; Sitepu, Farida Gasing; Umar, Moh. Tauhid; Nur, Muhammad (Hasanuddin University, 2015)
White-spotted spinefoot, Siganus canalicullatus (Park, 1797) is one of the most economically importantherbivorous fish captured along the coast of Selayar Islands. The present work was undertaken to assess thelength-weight relationship and Fulton's K condition factors of this fish caught in the waters of the northern coastof Selayar Islands District. Those parameters were calculated separately for both sexes. A total of 498specimens of S. canaliculatus consisting of 265 males and 233 females were randomly collected on a monthlybasis between January and June 2015 from local fishermen using gill nets of various mesh size in the coastalwaters of Desa Barat Lambongan, Kecamatan Bontomatene, northern part of Selayar Islands District. The fishwere brought to the laboratory and, after washing, their total length (L) was measured to the nearest 1 mm usinga fish measuring board and the total body weight (W) was recorded to the nearest 0.01 g using an electronicbalance. Each fish was then cut open and the sex were recorded. The length-weight relationships of males andfemales can be expressed as log W = –4.4220 + 2.7772 log L for males, indicated hypoallometric growthpattern; and log W = –4.6840 + 2.9022 log L for females, indicated isometric growth pattern. Overall, conditionfactor values were higher in males than in females.Keywords: condition factor, length-weight relationship, Selayar Islands District, Siganus canaliculatus, whitespottedspinefoot